Hospitality Industry in Russia: Key Problems and Solutions - ROMANYUK, Anton V.; GAREEV, Roman R. (Journal of Environmental Management and Tourism, 2019)
The aim of the present research is to study the condition and development of the Russian hotel market under the crisis. In the course of the present work the methods of systematic approach, economic and statistical analyses, quantitative and qualitative studies have been applied. Such methods allow to reveal the problems and prospects of the Russian hotel market development. The article presents the results of analyzing the state of the Russian hotel market. Authors identified factors hindering the development of the hospitality: worn out and outdated rooms in most hotels; high costs of labor, its training and retraining; high interest rates for financing new hotel development projects; high cost of housing and utility; high land tax rates; high property tax rate. The authors of the research have emphasized the necessity of the holding of the anti-crisis measures, aimed at the adjustment of the approaches to the hotel business management under the condition of the fluctuating market. The top priority steps are: reduce the value-added tax for hotel businesses, reduce the land tax for the hotel businesses, reduce the property tax, reduce the administrative burden on the hotel staff on migration registration of foreign and Russian citizens, create rules for providing hotel services in such a way that they protect the rights of not only consumers, but also hotels. As a result of the research the necessity of reforming the system of interaction between the hotel business and the government has been proved. All authors` references aim at the overcoming the negative tendencies on the Russian hotel market, caused by current crisis.